A telecom operator in West Africa - Doucoure, Fatoumata; Flouvat, Catherine (Technical Centre for Agricultural and Rural Cooperation, 2013)
With a presence in 18 African countries, Orange is an important telecom operator in Africa. Making its services available to small farmers is one of the company's priorities.